Is there a size difference between red and blue globular clusters? - Downing, Jonathan Michael Blake (Monthly notices of the Royal Astronomical Society, 2012)
Blue (metal-poor) globular clusters are observed to have half-light radii that are ∼20 per cent larger than their red (metal-rich) counterparts. The origin of this enhancement is not clear and differences in either the luminosity function or in the actual size of the clusters have been proposed. I analyse a set of dynamically self-consistent Monte Carlo globular cluster simulations to determine the origin of this enhancement. I ﬁnd that my simulated blue clusters have larger half-light radii due to differences in the luminosity functions of metal-poor and metal-rich stars. I ﬁnd that the blue clusters can also be physically larger, but only if they have a substantial number of black holes dynamically heating their central regions. For some combinations of metallicity and initial conditions the difference in luminosity function is sufﬁcient to explain the observed effect while for other combinations the size enhancement due to black holes is necessary to match the observations. I conclude that the observed difference in half-light radii between red and blue globular clusters is due to a combination of differences in size and luminosity function. I ﬁnd an additional corollary: the half-light radius is not a straightforward proxy for cluster size.